2022
DOI: 10.1590/fst.27421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gelatin-based active coatings formulated with rosemary extract on quality of cold stored meatballs

Abstract: Meatballs were coated by gelatin-based mixes incorporated with potassium sorbate and rosemary extract. Coated samples were evaluated by free fatty acids (FFAs), thiobarbituric acid reactive substances (TBARS), and total volatile basic nitrogen (TVB-N) content. In addition, texture profile analysis (TPA) was performed to evaluate the textural features of meatballs. Uncoated sample as control along with 3 other samples coated by different formulations were stored in zipped plastic bags at +4 °C for 10 days. No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…In the control group, these values were determined as 155.18 and 148.75 (N/mm 2 ), respectively. Torusdağ et al [36] reported that gelatin-based rosemary extract containing edible coatings reached lower chewing and stickiness values in beef patties compared to the control group after 10 days of storage, just like our result. In another study [37], the application of an edible coating enriched with antioxidant and antimicrobial substances to fish fillets at the end of storage, unlike our study, was determined to have the highest springiness.…”
Section: Resultssupporting
confidence: 86%
“…In the control group, these values were determined as 155.18 and 148.75 (N/mm 2 ), respectively. Torusdağ et al [36] reported that gelatin-based rosemary extract containing edible coatings reached lower chewing and stickiness values in beef patties compared to the control group after 10 days of storage, just like our result. In another study [37], the application of an edible coating enriched with antioxidant and antimicrobial substances to fish fillets at the end of storage, unlike our study, was determined to have the highest springiness.…”
Section: Resultssupporting
confidence: 86%
“…Meanwhile, proteases that can decompose the muscle protein of crayfish were secreted to further promote the deamination and decarboxylic reaction of amino acids in crayfish meat, thereby producing ammonia, amine, and other alkaline nitrogen-containing substances. Accordingly, TVB-N content continued to increase (Torusdağ et al, 2022;Kuswandi et al, 2011). With increased temperature, TVB-N content significantly increased (P < 0.05).…”
Section: Tvb-n In Crayfish Meat During Storagementioning
confidence: 89%
“…During storage, a decrease in pH may be due to the accumulation of deaminated protein, organic acid, and microbial metabolites formed as a result of enzymatic activity and the growth of microorganisms. Microorganisms metabolize carbohydrates and other compounds present in meat to produce lactic acid and acetic acid which results in a decrease in the pH of the system [41]. The results showed that the decrease in pH of fish gelatin-incorporated meatballs was lower than the Control and Branded Meatballs.…”
Section: Phmentioning
confidence: 97%